Differentiation and authentication of fishes at the species level through analysis of fish skin by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry. (17th July 2019) - Bi, Hongyan; Zhong, Chunyi; Shao, Mingke; Wang, Chengyu; Yi, Jia; Qiao, Liang; Zhang, Junbo
Abstract : Rationale: Authentication of fish is of importance in the view of toxins, allergen warnings and economic fraud control. Traditional methods in the authentication of fish, e.g. morphological, genetic and proteomic analysis, are either at low throughput or at high‐cost. Methods: A high‐throughput matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI TOF MS)‐based approach was developed to analyze biomaterials from fish skin, and mass spectra from different fish species were compared by chemometric methods to differentiate fish species. Results: A total of 51 fish samples were used to generate more than 150 fingerprinting mass spectra. The fish belonging to the same genus can be identified at species level. A mass spectral database of different fishes can be built as reference for authentication. The analysis can be performed based on micrograms of fish‐skin sample and accomplished in 1–3 hours. Conclusions: The developed strategy holds potential to be applied to fish authentication in the fishing industry and as a scientific method to avoid mislabeling. It has promise to be practically used for fast and effective identification of closely related fish species to guarantee the quality of fishery products to consumers.